Vocal development in nestling kea parrots (Nestor notabilis). Issue 2 (4th March 2021) - Wein, Amelia; Schwing, Raoul; Yanagida, Takuya; Huber, Ludwig
ABSTRACT: This study investigates vocal development of nestling kea parrots ( Nestor notabilis ). First, we examine how many structurally distinct call types were present during the nestling period, and the age in which call types occurred. Based on studies with other avian species, we predicted that kea nestlings would have multiple call types, with some present at hatching and others emerging later in the nestling period. Results showed that nestlings have four distinct call types, two present at hatching, and two emerging when the nestlings undergo large physical changes in the second week of life. While two of the call types developed gradually towards more adult-like structures, the other two did not and were apparently only used for communication in the nest. Second, we tested whether nestlings could be discriminated individually based on their calls. All four call types were individually discriminable from hatching until the end of the study, thus providing evidence for vocal signatures. While the function of vocal signatures cannot be ascertained from this study, kea breeding biology rules out explanations based on preventing misdirected parental care. We suggest that vocal signatures may be relevant to the division of parental resources in the nest.